Revelación (OUTING) como proceso en la aceptación social del género en estudiante de 17 años - Guaña Davila, Camila Carolina (2019)
This research is generated by a problem experienced by a 17-year-old adolescent of the Babahuyus Educational Unit, with the theme of study “Revelation (Outing) as a process of social acceptance of gender” in which emotional changes, anxiety are presented, worries and fears. Process that affects the personal, family and social area. For the collection of necessary and useful information for the study, it will be done through the management of medical records, semi-structured psychological interviews and the application of psychometric tests and projective tests, which will lead to a certain diagnosis in turn the data that obtained will contribute significantly to know the experiences, beliefs and perceptions experienced by both the family and adolescent system of a certain gender. For the management and possible solutions of this problem, it is appropriate to use a Systemic Family Therapy approach to improve assertive communication between each of the members who belong to the family and do not be afraid to talk about the sexual orientation of the patient and the Rational Emotional Behavioral Therapy for the modification of irrational beliefs that is had by certain sexual orientation